Plasma Choline as a Diagnostic Biomarker in Slow Coronary Flow. (25th January 2020) - Zhu, Yuan-Ting; Zhu, Ling-Ping; Wang, Zhen-Yu; Qiu, Xue-Ting; Wu, Wan-Zhou; Liu, Wei-Wang; Feng, Yu-Yu; Xiao, Wen-Kai; Luo, Xin; Li, Zhen-Yu; Li, Chuan-Chang
Abstract : Aim . The slow coronary flow (SCF) phenomenon was characterized by delayed perfusion of epicardial arteries, and no obvious coronary artery lesion in coronary angiography. The prognosis of patients with slow coronary flow was poor. However, there is lack of rapid, simple, and accurate method for SCF diagnosis. This study aimed to explore the utility of plasma choline as a diagnostic biomarker for SCF. Methods . Patients with coronary artery stenosis <40% evaluated by the coronary angiogram method were recruited in this study and were grouped into normal coronary flow (NCF) and SCF by thrombolysis in myocardial infarction frame count (TFC). Plasma choline concentrations of patients with NCF and SCF were quantified by Ultra Performance Liquid Chromatography Tandem Mass Spectrometry. Correlation analysis was performed between plasma choline concentration and TFC. Receiver operating characteristic (ROC) curve analysis with or without confounding factor adjustment was applied to predict the diagnostic power of plasma choline in SCF. Results . Forty-four patients with SCF and 21 patients with NCF were included in this study. TFC in LAD, LCX, and RCA and mean TFC were significantly higher in patients with SCF in comparison with patients with NCF (32.67 ± 8.37 vs. 20.66 ± 3.41, P < 0.01 ). Plasma choline level was obviously higher in patients with SCF when compared with patients with NCF (754.65 ± 238.18 vs. 635.79 ± 108.25, P = 0.007 ). Plasma choline level had significantly positive correlation with Mean TFC ( r = 0.364, P = 0.002 ). Receiver operating characteristic (ROC) analysis showed that choline with or without confounding factor adjustment had an AUC score of 0.65 and 0.77, respectively. Conclusions . TFC were closely related with plasma choline level, and plasma choline can be a suitable and stable diagnostic biomarker for SCF.